Empowering squatter citizen : local government, civil society, and urban poverty reduction - Mitlin, Diana; Satterthwaite, David (Earthscan, 2004)
Annotation This volume is the most recent addition to the examination of urban poverty by the Human Settlements Program at the International Institute for Environment and Development (IIED). It makes the case for redirecting support to local organizations and processes. The core of the book is case studies of innovative government organizations (in Thailand, Mexico, Philippines and Nicaragua) and community-driven processes (in India, South Africa, Pakistan and Brazil) that show new ways to address urban poverty. Each case study is prepared by specialists from these countries. They show that poverty reduction in urban areas is as much about building competent, accountable local organizations as about attempting to improve incomes. It involves strengthening and supporting the organizations formed by the poor or homeless to be able to develop their own solutions and able to negotiate better deals with the organizations delivering infrastructure, services, credit and land for housing. The understanding of urbanpoverty that the book presents goes beyond conventional, official definitions based only on income or consumption levels to include considerations of housing conditions, tenure, infrastructure and service provision, the rule of law, and civil and political rights, including 'voice' and the right to influence policy and practice on the ground. It offers powerful conclusions for national and local governments, NGOs and international agencies on how to tackle the complex and growing problem of urban poverty.
Keywords: Urban poor -- Government policy -- Developing countries -- Case studies.; Urban poor -- Services for -- Developing countries -- Case studies.; Pauvres en milieu urbain -- Politique gouvernementale -- Pays en voie de développement -- Études de cas.; Pauvres en milieu urbain, Services aux -- Pays en voie de développement -- Cas, Études de.; SOCIAL SCIENCE -- Poverty & Homelessness.; Urban poor -- Government policy; Urban poor -- Services for; Developing countries; Wohnungsnot; Stadtforschung; Armut; Schwellenländer; Armoede.; Empowerment.; Stedelijk beleid.; Assentamentos humanos.; Pobreza (redução); Políticas públicas.; Países em desenvolvimento.; Electronic books.; Case studies